Conocimiento de comprobantes de pago y su importancia fiscal en trabajadores de Electro Oriente SA Iquitos primer trimestre año 2024 - Bardales Barreto, Erick Anthony (2025)
The objective of the study was to determine the level of knowledge of payslips and their tax importance among Electro Oriente SA Iquitos employees in the first quarter of 2024. The study used was basic and the design was non experimental. It also provided relevant results, such as a fairly favorable level of knowledge of payslips and their tax importance. Therefore, the clinical work showed that the level of knowledge of payslips and their tax importance is high, with 59% reporting good knowledge and 68% reporting good tax importance.